Evaluation of the Implementation of Community-Based Total Sanitation Program (STBM) With Diarrhea - Dewi Haryanti; Mappeaty Nyorong; Endang Maryanti; Indah Anggraini; Ismail Effendy (Newinera Publisher, 2022)
Community Based Total Sanitation (STBM) is a method of changing sanitation behavior by empowering the community through the use of the triggering method. The STBM program has been implemented in Batu Bara Regency, especially the Tanjung Tiram Health Center. The purpose of this study was to evaluate a community-based total sanitation program with the incidence of diarrhea in Batu Bara Regency (Case Study of Tanjung Tiram Health Center, Tanjung Tiram District). The type of research used is descriptive qualitative with a case study design as a whole, the location of this research is in Batu Bara Regency (case study of Tanjung Tiram Health Center, Tanjung Tiram District). The informants in this study consisted of 5 respondents (Head of Environmental Health Section, Manager of Environmental Health Program of the Health Office, Head of Public Health Center, Manager of Environmental Health Program of Public Health Center and Village Head). The results of the study were seen from the input factors (human resources, funds and facilities and infrastructure were not sufficient), process factors (planning, organization were not adequate while the implementation had been carried out starting from triggering to verification of stopping open defecation, but after Monev was carried out it had not happened. changes), the output factor (there has been no increase in access to sanitation in the Tanjung Tiram Health Center work area) and the outcome factor (there has been no decrease in diarrhea cases in the Tanjung Tiram Health Center area).